Shear bioreactors stimulating chondrocyte regeneration, a systematic review - Negar sharifi; Anneh Mohammad Gharravi (BMC, 2019)
Abstract It is commonly accepted that the mechanical stimuli are important factors in the maintenance of normal structure and function of the articular cartilage. Despite extensive efforts, the cellular mechanisms underlying the responses of articular chondrocytes to mechanical stresses are not well understood. In the present review, different types of shear bioreactor and potential mechanisms that mediate and regulate the effect of shear on chondrocyte are discussed. For this review, the search of the literature was done in the PubMed, Scopus, Web of sciences databases to identify papers reporting data about shear on chondrocyte. Keywords "shear, chondrocyte, cartilage, bioreactor" were used. Studies published until the first of March 2018 were considered in this paper. The review focused on the experimental studies conducted the effect of shear stress on cartilage tissue in vivo and in vitro. In this review, both experimental studies referring to human and animal tissues were taken into account. The following articles were excluded: reviews, meta-analysis, duplicate records, letters, and papers that did not add significant information. Mechanism of shear stress on chondrocyte, briefly can be hypothesized as (1) altered expression of aggrecan and collagen type II, (2) altered cartilage oligomeric matrix protein (COMP) serum levels, consequently, organizing the arrangement binding of glycosaminoglycans, integrins, and collagen, (3) induction of apoptosis signals, (4) altered expression of integrin.